Honey consumption in the state of São Paulo: a risk to human health? - Rall, VLM; Bombo, A.; Lopes, T. F.; Carvalho, L. R.; Silva, Marcia Guimarães da [UNESP] (Elsevier B.V., 2003)
Infantile botulism was recognized in 1976 as a paralyzing disease caused by the ingestion of viable spores that would germinate and colonize the intestinal tract of infants, with local production and absorption of Clostridium botulinum toxin. The possible origins of botulinic spores are dust and honey, which has been identified as a dietary risk factor for infantile botulism. The objectives of the present study were to investigate 100 honey samples obtained in the state of São Paulo (Brazil) in terms of incidence of botulinic spores and of microbiologic quality, in agreement with Decree 367/9. All 100 samples analysed were negative for the presence of Salmonella, Shigella, total coliforms. C botulinum spores were present in 3 samples (3%) and molds and yeasts, in 64 samples (64%), but only 25 (25%) exceeded established criteria, with counts ranging from zero to 1.5 x 10(5) CFU/g. The presence of small sporogenic Gram-positive rods was observed in 42 (42%) of the 100 samples tested but these bacteria were not identified. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: infantile botulism; Clostridium botulinum; honey; foodborne disease; Brazil